Ovarian Tumors in Pregnancy: Diagnosis and Management - Husseinzadeh, Nader; Sibai, Baha; Siddiqi, Tariq A. (American Journal of Perinatology, 2012)
Ovarian tumors first diagnosed during pregnancy often present a challenge for both the obstetrician and gynecologists providing pregnancy care and for the consulting subspecialists. Although the vast majority of these tumors is benign, on rare occasions, patients present with tumors that turn out to be malignant requiring more comprehensive and extensive surgical procedures that are more likely to lead to pregnancy loss. Hence accurate knowledge of tumor characteristics, especially the ultrasound appearance and gestational age at diagnosis, are key prerequisite for establishing the most effective management plan not just for the index but also for future pregnancies. The primary objective of the current review is to provide practical guidelines for the evaluation and management of ovarian tumors first diagnosed during pregnancy.
Keywords: ovarian tumors; complicated pregnancy; management of ovarian tumors